Implementation of Deductions for Repayment of Murabahah Financing Debts Before Due Date : Case Study of Sharia Financial Institutions - Tamba, Dheddy Abdi; Mukhlas, Oyo Sunaryo; Rusyana, Ayi Yunus (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2023)
This research examines loan repayment at LKS (Sharia Financial Institutions) which provides reductions or deductions for debt repayment of debtors (customers) made before the maturity date of the murabahah contract. This research is also based on the frequent problems that arise between LKS (Sharia Financial Institutions) and customers regarding the absence of deductions for payments on murabahah contracts, because the rules for deductions are not included and are not agreed upon in the contract. This research method uses a descriptive qualitative method, namely with the subject and object being LKS, employees and debtors who use murabahah contract financing. And the data collection technique uses interview and documentation techniques. The research results explain that; (1) implementation of discounts for prepayment of remaining financing debts in murabahah financing transactions on LKS in Indonesia. This is the authority of the LKS in whether or not to grant deductions based on certain considerations, based on Fatwa DSN-MUIoNo.23/DSN-MUI/III/22002. In practice, customers can go directly to LKS to submit a request for a discount on payments before the due date. (2) The impact of deductions on repayment before the due date will have a positive impact on the Bank itself, namely creating trust in customers or consumers because they have given appreciation to customers who make repayment before the due date. Meanwhile, the postive impact for customers as business actors is getting relief. [Abstrak: Penelitian ini menelaah tentang pelunasan pinjaman pada LKS (Lembaga Keuangan Syariah) yang memberikan pengurangan atau potongan terhadap pelunasan utang debitur (nasabah) yang dilakukan sebelum jatuh tempo pada akad murabahah. Penelitian ini juga didasarkan dari sering munculnya permasalahan antara pihak LKS (Lembaga Keuangan Syariah) dan nasabah perihal tidak adanya potongan atas pelunasan pada akad murabahah, karena aturan potongan tidak dicantumkan dan tidak diperjanjikan didalam akad. Metode penelitian ini menggunakan metode kualitatif)deskripstif, yaitu dengan subjek dan objeknya LKS, pegawai serta debitur yang menggunakan)pembiayaan akad murabahah. Dan teknikkpengumpulan datanya dengan teknik wawancara dan dokumentasi. Hasil penelitian menjelaskan bahwa; (1) pelaksanaan pemberian potongan untuk pelunasan sisa utang pembiayaan sebelum waktunya dalam transaksi pembiayaan murabahah pada LKS yang ada di Indonesia. Hal ini hak kewenangan pihak LKS dalam pemberian potongan atau tidak dengan pertimbangan tertentu, yang berdasarkan Fatwa DSN-MUIoNo.23/DSN-MUI/III/22002. Pada pelaksanaannya nasabah bisa langsung mendatangi ke pihak LKS untuk mengajukan permohonan meminta potongan atas pelunasan sebelum jatuh tempo. (2) Dampak dari pemotongan pada pelunasan sebelum jatuhhtempo, akan berdampak positif bagi pihak Bank itu sendiri, yaitu menimbulkan kepercayaan kepada nasabah atau konsumen karena telah memberikan apresiasi kepada nasabah yang melakukan pelunasan sebelum jatuh tempo. Sedangkan dampak postiffbagi pihak nasabah sebagai pelaku usaha yaitu mendapatkan keringanan.]